دور التعليم العالي في الحراك الاجتماعي للمرأة الصحراوية في الجنوب الجزائري -دراسة ميدانية على عينة من طلبات جامعة الوادي- - لوحيدي, فوزي; الاسود, منال; الذهبي, ابراهيم (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة إلى تعرف على دور التعليم العالي في الحراك الاجتماعي للمرأة الصحراوية بالجنوب الجزائري، ولتحقيق أهداف الدراسة اتبعنا المنهج التحليلي الوصفي تم تطوير استبانه مكونه من (19 ) فقرة موزعه على مجالين هما: المجال الاجتماعي، والمجال الاقتصادي. وقد تألفت عينة الدراسة من(37) من طالبات جامعة الوادي , وقد أظهرت نتائج الدراسة أن درجة دور التعليم العالي في الحراك الاجتماعي للمرأة الصحراوية في الجنوب الجزائري من وجهة نظر أفراد العينة، جاءت متوسطة و عالية في المجال الثقافي ، وعالية في المجال الاقتصادي. كما أظهرت النتائج وجود فروق ذات دلاله إحصائية(α=0.05) على مجالي الدراسة ، في دور التعليم العالي في الحراك الاجتماعي للمرأة الصحراوية في الجنوب الجزائري ,من وجهة نظر الطالبات تعزى لمتغير مكان السكن ، ولصالح سكان المدينة وبينت نتائج الدراسة عدم وجود فروق ذات دلالة إحصائية (α=0.05) في دور التعليم العالي في الحراك الاجتماعي للمرأة الصحراوية في الجنوب الجزائري ,من وجهة نظر الطالبات تعزى لمتغير دخل الأسرة . Abstract: This study aims to identify the role of higher education in the social mobility of Desert women in southern Algeria, and to achieve the aims of the study. a questionnaire was developed consisting of (19) items, which included two areas: The social area, the economic area. The study sample consisted of (37) students from ELUOED University. The results of the study showed that the degree of the role of higher education in the social mobility of Desert women in southern Algeria, from the point of view of the sample, was medium and high in the cultural area, and high in the economic area. The results also showed the presence of statistically significant differences (α = 0.05) on the two fields of study, in the role of higher education in the social mobility of Desert women in southern Algeria, from the viewpoint of students attributed to the variable of the place of residence, and for the benefit of the residents of the city and the results of the study showed that there are no significant differences Statistics (α = 0.05) in the role of higher education in the social mobility of Desert women in southern Algeria
The role of higher education in the social mobility of Sahrawi women in southern Algeria A field study on a sample of Al-Wadi University application
مقال
Keywords: المرأة ، التعليم ، التعليم العالي، الحراك الاجتماعي، الصحراء; social, mobility , education, higher education , Desert women